Foil Method of Multiplying Binomials

Foil Method of Multiplying Binomials

<p> Foil Method of Multiplying Binomials</p><p>1. Multiply the First terms of each binomial. 2. Multiply the Inside terms and Outside terms of the product. Combine like terms. 3. Multiply the Last two terms of each binomial.</p><p>F L F L F O I L Multiply using FOIL: (x + 3 ) ( x + 2) = _ x 2_ +2x_ _+3x_ _+6_ = x2 + 5x + 6 O I I O</p><p>Notice that the two inside terms are like terms that can be added together. This method is known as the FOIL method. It gets its name from the process:</p><p>Try these. 4x+ 5x</p><p>1. (x + 4) ( x + 5 ) = _ x 2_ __+9x_ __+20 = x2 + 9x + 20</p><p>2. (x + 1) ( x + 3 ) = ______</p><p>3. (x + 7) ( x + 3 ) = ______</p><p>4. (x + 5) ( x + 6 ) = ______</p><p>5. (x + 8) ( 2x + 9 ) = ______</p><p>35x+7x 6. (5x + 6) ( x + 7 ) = _ 5x 2_ _+41x _+42_ = 5x2 + 41x + 42</p><p>7. (x + 2) ( 3x + 5 ) = ______</p><p>8. (3x + 8) ( 5x + 6 ) = ______</p><p>9. (x - 5) ( x – 4 ) = ______</p><p>10. (x - 8) (x – 3 ) = ______</p><p>11. (x - 2) (x – 4 ) = ______</p><p>12. (2x - 1) (x – 3 ) = ______</p><p>13. ( x - 5) (3x – 4 ) = ______</p><p>14. (2x – 3) (4x – 5) = ______</p><p>15. (2x - 5) ( 3x – 4 ) = ______</p><p>16. (2x - 5) ( x – 4 ) = ______</p><p>DIFFERENT SIGNS: +5x – 4x</p><p>1. (x - 4) ( x + 5 ) = _ x 2_ __+1x__ __-20__ = x2 + x - 20 2. (x + 1) ( x - 3 ) = ______</p><p>3. (x - 7) ( x + 3 ) = ______</p><p>4. (x + 5) ( x - 6 ) = ______</p><p>5. (x - 8) ( 2x + 9 ) = ______</p><p>6. (5x + 6) ( x - 7 ) = ______</p><p>7. (x - 2) ( 3x + 5 ) = ______</p><p>8. (3x + 8) ( 5x - 6 ) = ______</p><p>9. (x + 5) ( x – 4 ) = ______</p><p>10. (x - 8) ( x + 3 ) = ______</p><p>11. (x + 2) ( x – 4 ) = ______</p><p>12. (2x - 1) ( x + 3 ) = ______</p><p>13. ( x + 5) (3x – 4 ) = ______</p><p>14. (2 x – 3) (4 x + 5) = ______</p><p>15. (2x - 5) ( 3x + 4 ) = ______</p><p>16. (2x + 5) ( x – 4 ) = ______</p><p>17. ( x+ 3) ( x – 3) = ______</p><p>18. ( x+ 4) ( x – 4) = ______</p><p>19. ( x - 2 ) ( x + 2) = ______</p><p>20. ( x+ 7) ( x – 7) = ______</p><p>21. ( x – 9 ) ( x + 9 ) = ______</p><p>Evaluate for the given value(s) of the variable:</p><p>1. x2 + 4x - 5 for x = 2 2. 3x2 - 3x for x = -2 3. -2x2 - 4x + 5 for x = -3</p><p>4. x2 - 3xy + y2 for x = -1, y = 2 5. 2xy - x2 - 2y for x = -2, y = 3 </p><p>H.W. Finish worksheet and Pg 218: odds 47-53; Pg 250: 1, 2, 3 (ans.to 2: 85) (034) Multiply using FOIL: Pg. 243: all 5-10, 13, 23, 24, all 37-41, 51, 52</p>

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    2 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us